Metaphorical Meanings. Do you see what I mean? - Marga Reimer (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
My intention in this paper is to propose a conception of metaphorical meaning on which the meaning of a metaphor includes propositional as well as non-propositional features. I will make two general claims on behalf of the proposed account: first, it is intuitive; second, it is of theoretical value. In claiming that the proposed account is of theoretical value, I mean only that its adoption leads to an increased understanding of the nature of metaphor: of metaphorical thought and ofmetaphorical communication in particular.
Keywords: Philosophy; linguistics